PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, TRANSAKSIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DINAS PERTANIAN KABUPATEN BONDOWOSO - Lutfi, Moch; Azhad, Muhammad Naely; Saidah, Nur (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aims to examine and analyze the influence of transformational, transactional and work discipline leadership styles on the performance of Bondowoso Agricultural Service employees. This type of research. causality research, namely research that explains the relationship that influences each other between the independent variable and the dependent variable. The population in this study were Bondowoso Agriculture Office employees, the sample used was 100 respondents. The analysis tool uses multiple linear analysis. The results of the study prove that transformational, transactional and work discipline leadership styles have a significant effect on the performance of Bondowoso Agricultural Service employees.